FPGA Based Online Data Acquisition System (DAS) for Optical Tomography Application - Muji, SIti Zarina (International Journal of Integrated Engineering, 2017)
This paper presents the development of online data acquisition unit for Optical Tomography (OT) system based on Field Programmable Gates Array (FPGA). This design is to overcome the long conversion delay in Analog to Digital Converter (ADC) using a microcontroller that has been proposed previously for OT system although FPGA has been used in other type of tomography systems. The main purpose of this design is to log the sensor data into the computer through Universal Asynchronous Receiver/Transmitter (UART). The developed system consists of three main units which are: (1) measurement unit, (2) control unit and (3) image reconstruction unit. In the measurement unit, 16 pairs of transmitters and receivers are arranged around the sensor jig connected to the corresponding light projection circuit for transmitters and signal conditioning circuit for receivers. The light projection signals and the received data are controlled by the Altera DE2-115 FPGA which assigned as the main control unit. Then, the sensor data are transferred into computer for the image reconstruction process using Filtered Back Projection (FBP) algorithm. Based on Mean Structutal Similarity Index (MSSIM), the similarity index for the reconstructed images of the real object and the modelling object are 0.89 for object with diameter 21.5 mm and 0.88 for object with diameter 33.5 mm.